Pengaruh Pemupukan terhadap Peningkatan Produksi dan Kualitas Buah Jambu Biji (Psidium guajava L.) - PRATAMA, GHADING SEPTA; RAI, I NYOMAN; WIRAATMAJA, I WAYAN (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2023)
The Effect of Fertilization on Increasing Production and Quality of Guava Fruit ( Psidium guajava  L.) This study aimed to determine the effect of fertilization on increasing production and quality of Guava Fruit. The study was carried out at the Experimental Garden of the Faculty of Agriculture Udayana University, from January to June 2022. The study used a randomized block design with a single factor and 6 replications, the treatments was fertilization consisted of 4 levels i.e., without fertilizer (P t ), fertilized with compost only (P k ), fertilized with compost + macro fertilizer N, P, K, and Ca, (P m ) and fertilized with compost + macro fertilizer N, P, K, and Ca + micro fertilizer ZnSO4 and CuSO4 (P b ). The results showed that the highest fruit weight per tree (4843.65 g) obtained at the fertilization with compost + macro fertilizer N, P, K, and Ca (P m ). Fertilization with compost + macro fertilizer N, P, K, and Ca (P m ) also gave the highest number of fruits formed per tree, number of harvested fruits per tree, level of sweetness of the fruit, and leaf chlorophyll.